WMJ-S-001, a Novel Aliphatic Hydroxamate-Based Compound, Suppresses Lymphangiogenesis Through p38mapk-p53-survivin Signaling Cascade - Huang, Shiu-Wen; Yang, Hung-Yu; Huang, Wei-Jan; Chen, Wei-Chuan; Yu, Meng-Chieh; Wang, Shih-Wei; Hsu, Ya-Fen; Hsu, Ming-Jen (Frontiers in Oncology, 2019)
Background and purpose: Angiogenesis and lymphangiogenesis are major routes for metastatic spread of tumor cells. It thus represent the rational targets for therapeutic intervention of cancer. Recently, we showed that a novel aliphatic hydroxamate-based compound, WMJ-S-001, exhibits anti-angiogenic, anti-inflammatory and anti-tumor properties. However, whether WMJ-S-001 is capable of suppressing lymphangiogenesis remains unclear. We are thus interested in exploring WMJ-S-001's anti-lymphangiogenic mechanisms in lymphatic endothelial cell (LECs). Experimental approach: WMJ-S-001's effects on LEC proliferation, migration and invasion, as well as signaling molecules activation were analyzed by immunoblotting, flow-cytometry, MTT, BrdU, migration and invasion assays. We performed tube formation assay to examine WMJ-S-001's ex vivo anti-lymphangiogenic effects. Key results: WMJ-S-001 inhibited serum-induced cell proliferation, migration, invasion in murine LECs (SV-LECs). WMJ-S-001 reduced the mRNA and protein levels of survivin. Survivin siRNA significantly suppressed serum-induced SV-LEC invasion. WMJ-S-001 induced p53 phosphorylation and increased its reporter activities. In addition, WMJ-S-001 increased p53 binding to the promoter region of survivin, while Sp1 binding to the region was decreased. WMJ-S-001 induced p38 mitogen-activated protein kinase (p38MAPK) activation. p38MPAK signaling blockade significantly inhibited p53 phosphorylation and restored survivin reduction in WMJ-S-001-stimulated SV-LCEs. Furthermore, WMJ-S-001 induced survivin reduction and inhibited cell proliferation, invasion and tube formation of primary human LECs. Conclusions and Implications: These observations indicate that WMJ-S-001 may suppress lymphatic endothelial remodeling and reduce lymphangiogenesis through p38MAPK-p53-survivin signaling. It also suggests that WMJ-S-001 is a potential lead compound in developing novel agents for the treatment of lymphangiogenesis-associated diseases and cancer.